2015
DOI: 10.1007/s00382-015-2654-6
|View full text |Cite
|
Sign up to set email alerts
|

Troposphere–stratosphere response to large-scale North Atlantic Ocean variability in an atmosphere/ocean coupled model

Abstract: The instrumental records indicate that the basin-wide wintertime North Atlantic warm conditions are accompanied by a pattern resembling negative North Atlantic oscillation (NAO), and cold conditions with pattern resembling the positive NAO. This relation is well reproduced in a control simulation by the stratosphere resolving atmosphere–ocean coupled Max-Planck-Institute Earth System Model (MPI-ESM). Further analyses of the MPI-ESM model simulation shows that the large-scale warm North Atlantic conditions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 62 publications
(89 reference statements)
4
43
1
Order By: Relevance
“…Rather, they seem to amplify the NAO response when the signal that emerges in the stratosphere reaches the surface. These results differ from Omrani et al (2015) that found a stratospheric response in both a standalone and an oceanatmosphere coupled version of their model. Nonetheless, this response was smaller in the coupled version, which is consistent with SLAB-OCEAN in suggesting that the ocean-atmosphere coupling dampens the response of the stratosphere.…”
Section: Response Of the Stratosphere And Downwardcontrasting
confidence: 99%
See 1 more Smart Citation
“…Rather, they seem to amplify the NAO response when the signal that emerges in the stratosphere reaches the surface. These results differ from Omrani et al (2015) that found a stratospheric response in both a standalone and an oceanatmosphere coupled version of their model. Nonetheless, this response was smaller in the coupled version, which is consistent with SLAB-OCEAN in suggesting that the ocean-atmosphere coupling dampens the response of the stratosphere.…”
Section: Response Of the Stratosphere And Downwardcontrasting
confidence: 99%
“…In these studies, the AMV-related SST anomalies induce a negative NAO/ NAM response in winter in atmospheric general circulation models (AGCMs), that is associated with a southward shift of the North Atlantic storm track (Msadek et al 2011;Omrani et al 2014;Peings and Magnusdottir 2014a;Davini et al 2015). Some coupled ocean-atmosphere simulations also support this relationship (Kavvada et al 2013;Gastineau et al 2013;Ba et al 2014;Ruprich-Robert and Cassou 2014;Omrani et al 2015), as do statistical analyses of observations/reanalyses from the 20th century (Peings and Magnusdottir 2014a). The AMV has also been found to modulate the probability of atmospheric blocking events in the North Atlantic sector (Häkkinen et al 2011).…”
Section: Introductionmentioning
confidence: 91%
“…: Schimanke et al 2011;Reichler et al 2012;Woo et al 2015;Omrani et al 2016) and there is still a lot of uncertainty in this topic. The analysis of multi-decadal changes in the ENSO-related stratospheric teleconnection would be extremely relevant since these changes might contribute to the interdecadal variability of EN signal over Europe and it would then help to provide a complete picture of the non-stationary ENSO impacts over this area.…”
Section: Introductionmentioning
confidence: 99%
“…This is different from the present climate, where a stronger high pressure and persistent snow cover over Eurasia might enhance the upward propagation of the planetary waves from the troposphere to the stratosphere (e.g., Allen and Zender, 2011;Cohen et al, 2012;Kim et al, 2014). One possible reason is that only 3 out of the 11 models have a well-resolved stratosphere, which is crucial for simulating the midlatitude atmospheric response associated with the troposphere-stratosphere interaction (Omrani et al, 2014(Omrani et al, , 2016Nakamura et al, 2015;Zhang et al, 2017).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Indeed, the stronger SST warming over the North Atlantic could enhance the poleward ocean heat transport and could then melt more sea ice (Mahlstein and Knutti, 2011;Jung et al, 2017;Nummelin et al, 2017). The basin-wide Atlantic warming is also crucial for the negative tendency of the NAO, via an atmospheric wave train (Sato et al, 2014) and troposphere-stratosphere interaction (Omrani et al, 2016). The atmospheric response to the sea-ice decline might also be highly nonlinear (Petoukhov and Semenov, 2010).…”
Section: Summary and Discussionmentioning
confidence: 99%